2014
DOI: 10.3389/fpubh.2013.00076
|View full text |Cite
|
Sign up to set email alerts
|

School Environment and School Injuries

Abstract: Background: Although injuries at school are an important issue in public health, environmental factors in schools and school yards have seldom been the focus of school injury research. The goal of our investigation was to examine the effect of environmental factors on school injuries.Methods: Nine comprehensive Finnish schools registered school injuries over a period of two school years. Injuries were classified as being associated with environmental factors, suspected environmental factors, and others. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 39 publications
1
16
1
1
Order By: Relevance
“…The present study noted more indoor injuries. The result is in contrast to those of other studies . Indoor injuries happened mostly in the classrooms and corridors, while outdoor injuries happened in the garden.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study noted more indoor injuries. The result is in contrast to those of other studies . Indoor injuries happened mostly in the classrooms and corridors, while outdoor injuries happened in the garden.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with the research in Turkey and other countries, the present study also showed that boys had more injuries than girls. In other words, being a boy is an important risk factor for school‐based injuries . Furthermore, the incidence of ≥two injuries was higher for boys.…”
Section: Discussionmentioning
confidence: 98%
“…1,4,5 Considering that children spend most of their time at the school, actions to improve the school environment and to promote health practices could reduce the occurrence of these traumatic episodes. 14,[16][17][18][19][20] The evaluation of the contextual factors related to the physical structure of the schools that could be associated with the higher prevalence of TDI, as well as of health practices that could reduce the occurrence of this oral health problem, would be the first step to identify appropriate measures to be taken by the school coordinators in order to protect the students' teeth against dental trauma. In this context, it was observed that some factors related to the school environment were associated with a lower prevalence of TDI in the 12 years old students, such as schools with soft patio floors, access ramps, and schools that promoted health practices for their students.…”
Section: Discussionmentioning
confidence: 99%
“…Since TDIs affect young children and adolescents, it is expected that a great part of these injuries occurs in schools. [12][13][14] Therefore, investigation of contextual factors related to the school environment could support some actions aiming to reduce the occurrence of TDIs. Such actions could target a safer school physical structure, 15 as well as the implementation of health promoting schools.…”
Section: Introductionmentioning
confidence: 99%
“…In Bezug auf die übrigen Individualmerkmale ist die Befundlage hingegen eindeutiger: Demnach verletzen sich Jungen häufiger in der Schule als Mädchen [12][13][14][15][16]. Chau [14] form deckt sich dieser Befund mit Ergebnissen aus anderen Studien [12,20], während regionale Unterschiede bei Verletzungen im Kindesalter an anderer Stelle sehr wohl vorzufinden sind [3,22]. Neben der Darlegung konkreter Wirkungszusammenhänge möchte der vorliegende Beitrag auch dafür sensibilisieren, die verschiedenen Verletzungsorte im Kontext Schule differenziert zu betrachten.…”
Section: Diskussionunclassified